Phytotoxic effects of Echinochloa colona (L.) Link. (Poaceae) extracts on the germination and seedling growth of weeds - Gomaa, N. H.; AbdElgawad, H. R. (Spanish Journal of Agricultural Research, 2012)
This paper aims to study the phytotoxic potential of Echinochloacolonain order to explore its potential as bioherbicide. In this way, the phytotoxic effects of the most active fraction and pure compound from methanol (MeOH) extract of E.colona shoots on germination and seedling growth of ten weed species and on E. colona itself were evaluated. A lettuce seed bioassay indicated that dichloromethane (CH2Cl2) solublefraction of MeOH extract had the most phytotoxic activity. The most phytotoxic active compound of CH2Cl2 fraction was isolated and identified as tricin. Different concentrations of CH2Cl2 fraction (100, 500, 1000 mg L-1) and tricin (50, 100, 200 µmol L-1) were used to assess their phytotoxicity on germination and seedling growth of Portulaca oleracea, Corchorus olitorius, Brachiaria reptans, Euphorbia heterophylla, Dinebra retroflexa, Hibiscus trionum, Amaranthus graecizans, Amaranthus hybridus, Convolvulus arvensis, Setaria pumila and E.colona. Low concentration of CH2Cl2 fraction (100 mg L-1) significantly stimulated germination and seedling growth of some test species. There was no significant effect of the low concentration of tricin (50µmol L-1) on germination and elongation of roots and shoots of species. Higher concentrations of CH2Cl2 fraction (500, 1000 mg L-1) and tricin (100, 200µmol L-1) inhibited germination and seedling growth of most species. The results suggest that CH2Cl2 fraction and tricin might be potentially useful as bioherbicide for weed control in agriculture.